2022
DOI: 10.1101/2022.05.23.22275201
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analytical validation of a multi-protein, serum-based assay for disease activity assessments in multiple sclerosis

Abstract: Purpose: To characterize and analytically validate the MSDA Test, a serum-based multiplex protein biomarker assay developed using Olink® PEA methodology. Experimental design: Two lots of the MSDA Test panel were manufactured and subjected to a comprehensive analytical characterization and validation protocol to detect biomarkers present in the serum of patients with MS. Biomarker concentrations were incorporated into a final algorithm used for calculating four Disease Pathway scores (Immunomodulation, Neuroin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…Leveraging the Proximity Extension Assay (PEA) methodology on the Olink™ platform, 28 a prior study reported the analytical characterization of a custom serum-based proteomic multiplex immunoassay (PMI) panel (including sNEFL and sGFAP) associated with inflammatory MS disease activity and pertaining to key biological pathways in MS pathogenesis. 29 Here, we deployed statistical learning methods to examine the association between serum biomarker profiles using the custom PMI panel and patient-reported disability in pwMS. Specifically, we hypothesized that serum protein profiles informative of inflammatory MS disease activity would also improve the prediction of real-world neurological disability when compared to clinical profiles or single serum protein.…”
Section: Introductionmentioning
confidence: 99%
“…Leveraging the Proximity Extension Assay (PEA) methodology on the Olink™ platform, 28 a prior study reported the analytical characterization of a custom serum-based proteomic multiplex immunoassay (PMI) panel (including sNEFL and sGFAP) associated with inflammatory MS disease activity and pertaining to key biological pathways in MS pathogenesis. 29 Here, we deployed statistical learning methods to examine the association between serum biomarker profiles using the custom PMI panel and patient-reported disability in pwMS. Specifically, we hypothesized that serum protein profiles informative of inflammatory MS disease activity would also improve the prediction of real-world neurological disability when compared to clinical profiles or single serum protein.…”
Section: Introductionmentioning
confidence: 99%
“…Full details on the algorithm and model parameters are presented elsewhere. 23 Single-protein models were fit using L2-penalized logistic regression with presence or absence of Gd+ lesions as the dependent variable and an intercept and the protein biomarker as independent variables. Protein concentrations were limit of quantitation (LOQ)-imputed, log 10transformed, and demographically adjusted (with age and sex, based on Ordinary Least Squares [OLS] modeling) prior to being used in the Disease Pathway, Disease Activity, and single-protein models.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research and development studies, samples from a cohort of healthy controls, and those from the Train subset were used to establish the biomarker-specific demographic adjustment strategy, which included removing protein concentration outliers, accounting for OLS coefficient sign consistency across the three studies and establishing statistical significance related to both age and sex. 23 Metrics for model performance including the area under the receiver operating characteristic (AUROC), sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), accuracy, and odds ratios were used to evaluate model performance. The prevalence of Gd+ lesions was enriched in this dataset, and it is important to note that PPV, NPV, and accuracy all depend on the prevalence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations